2014
DOI: 10.1111/j.1468-0475.2012.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Bequest Motives and the Demand for Life Insurance in East Germany

Abstract: Empirical studies of household saving remain inconclusive about the role of bequest motives. This may be due to the diluting effect of different tax regimes across countries and time on estimates of bequest motives. Relative to market‐based economies, the former German Democratic Republic can be viewed as an experimental institutional setting where life‐insurance demand was not influenced by tax considerations. This allows isolating bequest motives from other life‐cycle and precautionary savings motives. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In general, the demand for the LIP increases as individuals grow a family and decreases as they age. This depicts that the consumers' age and the demand for the LIP are related non-linearly (Brighetti et al, 2014;Buric et al, 2017;Chen et al, 2001;Frees & Sun, 2010;Luciano et al, 2016;Sauter, 2014;Tan et al, 2009).…”
Section: Individual-related Antecedentsmentioning
confidence: 92%
See 1 more Smart Citation
“…In general, the demand for the LIP increases as individuals grow a family and decreases as they age. This depicts that the consumers' age and the demand for the LIP are related non-linearly (Brighetti et al, 2014;Buric et al, 2017;Chen et al, 2001;Frees & Sun, 2010;Luciano et al, 2016;Sauter, 2014;Tan et al, 2009).…”
Section: Individual-related Antecedentsmentioning
confidence: 92%
“…However, as individuals age, their probability of death increases, leading to a rise in the face value of LIP and high premium payments. A couple of studies only found a positive relationship between age and demand for life insurance since they considered respondents of age less than 55 years and of the mean age of 31 years, respectively (Sauter, 2014;Tan et al, 2009). In contrast, few studies also found the negative effect of age on demand for life insurance.…”
Section: Individual-related Antecedentsmentioning
confidence: 99%
“…Although both find that bequest motives shape savings behavior, altruism toward one's children appears to be of only minor importance. In contrast, Inkmann and Michaelides (2012) and Sauter (2014) find evidence for the existence of bequest motives in life insurance demand among households with children as well as for married couples in the UK and the former German Democratic Republic, respectively.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Powy ej opisana sytuacja, szeroko rozumianej popularno ci takiej formy oszczdzania, ale równie lokowania kapita u, jest zwi zana z udogodnieniami, które by y oferowane podczas podpisywania takich umów (Sauter, 2014). Osoby zawieraj ce umow na ubezpieczenie na ycie nie p aci y podatku z generowanych zysków.…”
Section: Popularno Ubezpiecze Na Ycie Z Ubezpieczeniowym Funduszem Kaunclassified